Diseño y documentación de los requisitos de la norma técnica de calidad de la gestión pública (NTC GP 1000-2009) para los juzgados civiles circuitos de la rama judicial del poder público - Armenia, Quindío (2015)
This internship project was aimed to document the requirements of the NTC GP 1000: 2009 of the Civil Courts Circuit of the Judicial Branch (Department) in the city of Armenia Quindío. To fulfill this objective, it was conducted a descriptive research using the method of observation and the deductive one; making use of sources and data collection techniques such as interviews and other documents of interest in order to identify compliance requirements and essential characteristics of the quality law. The subjects of this research were two courts with a staff of 4 people each. Thus, the results are constituted in all the mandatory documentation required by the law and the aspects needed so that the Judicial Branch in Armenia maintain a Quality Management System. It is expected that this contribution fosters the achievement of the Quality Certification granted by ICONTEC, and improves service delivery in all its concerns. Likewise it is recommended to socialize and implement the Quality System under the parameters established for doing so. At the same time, updating and making appropriate decisions to improve it are always a must.